2021
DOI: 10.1021/acs.iecr.1c00175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Dispersed Palladium Nanoparticles Supported on Silica for Catalytic Combustion of Methane

Abstract: Palladium nanoparticles supported on silica catalysts (Pd/SiO 2 ) were prepared by wet impregnation (WI), dry impregnation (DI), strong electrostatic adsorption (SEA), and charge-enhanced dry impregnation (CEDI) methods. The Pd/SiO 2 samples with highly dispersed and tight size-distributed palladium nanoparticles are obtained via SEA and CEDI methods based on strong electrostatic interactions between the dissolved metal precursor ([Pd(NH 3 ) 4 ] 2+ ) and positively charged SiO 2 support in an alkali-impregnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
(188 reference statements)
0
12
0
Order By: Relevance
“…, 24 h at 350–400 °C , ); that is, successful activations generally exceed the time and temperature ranges explored here. Using relatively aggressive activations, successful conversions of 1000–10,000 ppmv methane (0.1–1% CH 4 , with 10% or less oxygen) at temperatures well below the ignition point (600 °C) have been recorded ,,,, with a few demonstrating conversion temperatures as low as 300 °C. , While the reaction temperatures we observed are moderately lower than previous demonstrations, the dramatically different activation procedures and simplified catalyst synthesis offer unique benefits. As a point of comparison, conversion efficiencies to CO 2 are not often reported and cannot be directly compared to our results; nevertheless, methanol production rates in previous studies have been quite low (order 0.1–0.3 mol methanol per mol Cu or less; methanol production was not systematically quantified in our study, but early spot checks in the two-step process revealed around 1–2 orders of magnitude lower methanol in the post-reaction, water-extracted catalyst, where the input methane was around 10 6 -fold lower than in previous studies).…”
Section: Results and Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…, 24 h at 350–400 °C , ); that is, successful activations generally exceed the time and temperature ranges explored here. Using relatively aggressive activations, successful conversions of 1000–10,000 ppmv methane (0.1–1% CH 4 , with 10% or less oxygen) at temperatures well below the ignition point (600 °C) have been recorded ,,,, with a few demonstrating conversion temperatures as low as 300 °C. , While the reaction temperatures we observed are moderately lower than previous demonstrations, the dramatically different activation procedures and simplified catalyst synthesis offer unique benefits. As a point of comparison, conversion efficiencies to CO 2 are not often reported and cannot be directly compared to our results; nevertheless, methanol production rates in previous studies have been quite low (order 0.1–0.3 mol methanol per mol Cu or less; methanol production was not systematically quantified in our study, but early spot checks in the two-step process revealed around 1–2 orders of magnitude lower methanol in the post-reaction, water-extracted catalyst, where the input methane was around 10 6 -fold lower than in previous studies).…”
Section: Results and Discussionmentioning
confidence: 60%
“…Limited but quantifiable conversion was observed at temperatures as low as 100 °C (Figure a), reduced from previous experiments carried out between 150 and 200 °C. Catalytic conversion of methane using PGMs, cobalt, or nickel–cobalt mixtures , has typically relied on higher activation temperatures (500–1000 °C) or long durations ( e.g. , 24 h at 350–400 °C , ); that is, successful activations generally exceed the time and temperature ranges explored here.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported studies of catalytic oxidation employ supported Pt and Pd, where the support is mainly a more accessible metal oxide such as aluminum oxide, cerium oxide, , and silicon dioxide , or metal such as nickel, barium, zeolite, and zirconium. , While such configurations are relevant for practical applications, they come with the complexity of the role played by the support and uncertainty of mechanisms explaining the interchanging reactions between noble metals, support, and gaseous reactants. Only a handful of papers are reported for pure unsupported noble metals reacting with a limited range of hydrocarbon fuels .…”
Section: Introductionmentioning
confidence: 99%
“…20−22 Further details may be found in the following comprehensive reviews on this topic. 23−27 Most reported studies of catalytic oxidation employ supported Pt and Pd, 28−33 where the support is mainly a more accessible metal oxide such as aluminum oxide, 34−38 cerium oxide, 39,40 and silicon dioxide 41,42 or metal such as nickel, 43 barium, 44 zeolite, 45 and zirconium. 46,47 While such configurations are relevant for practical applications, they come with the complexity of the role played by the support and uncertainty of mechanisms explaining the interchanging reactions between noble metals, support, and gaseous reactants.…”
Section: ■ Introductionmentioning
confidence: 99%